2018
DOI: 10.1002/2211-5463.12542
|View full text |Cite
|
Sign up to set email alerts
|

Glyceraldehyde‐3‐phosphate dehydrogenase from Citrobacter sp. S‐77 is post‐translationally modified by CoA (protein CoAlation) under oxidative stress

Abstract: Protein CoAlation (S‐thiolation by coenzyme A) has recently emerged as an alternative redox‐regulated post‐translational modification by which protein thiols are covalently modified with coenzyme A (CoA). However, little is known about the role and mechanism of this post‐translational modification. In the present study, we investigated CoAlation of glyceraldehyde‐3‐phosphate dehydrogenase ( GAPDH ) from a facultative anaerobic Gram‐negative bacterium Citrobacter sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 65 publications
(168 reference statements)
0
16
0
Order By: Relevance
“…In addition to intra/intermolecular disulfide bond formation, GAPDH can also form mixed disulfide bonds with LMW thiols, which serve as cellular redox buffers and contribute to the protection of proteins from H 2 O 2 and other oxidants [ 60 , 61 ]. GAPDH has been reported to form mixed-disulfides with various LMW thiols, including glutathione (GSH—eukaryotes and Gram-negative bacteria), bacillithiol (BSH—Gram-positive Firmicutes), mycothiol (MSH—Actinobacteria) and coenzyme A (CoA—all organisms) ( Figure 2 , Table 2 ) [ 20 , 40 , 46 , 47 , 58 , 59 , 62 ].…”
Section: Gapdh Modifications By Redox Writersmentioning
confidence: 99%
“…In addition to intra/intermolecular disulfide bond formation, GAPDH can also form mixed disulfide bonds with LMW thiols, which serve as cellular redox buffers and contribute to the protection of proteins from H 2 O 2 and other oxidants [ 60 , 61 ]. GAPDH has been reported to form mixed-disulfides with various LMW thiols, including glutathione (GSH—eukaryotes and Gram-negative bacteria), bacillithiol (BSH—Gram-positive Firmicutes), mycothiol (MSH—Actinobacteria) and coenzyme A (CoA—all organisms) ( Figure 2 , Table 2 ) [ 20 , 40 , 46 , 47 , 58 , 59 , 62 ].…”
Section: Gapdh Modifications By Redox Writersmentioning
confidence: 99%
“…In addition to intra/intermolecular disulfide bond formation, GAPDH can also form mixed disulfide bonds with LMW thiols, which serve as cellular redox buffers and contribute to the protection of proteins from H2O2 and other oxidants [60,61]. GAPDH has been reported to form mixed disulfides with various LMW thiols, including glutathione (GSH -eukaryotes and Gramnegative bacteria), bacillithiol (BSH -Gram-positive Firmicutes), mycothiol (MSH -Actinobacteria) and coenzyme A (CoA -all organisms) ( Figure 2 and Table 2) [20,40,46,47,58,59,62].…”
Section: Sulfenylation and S-thiolation Of Gapdhmentioning
confidence: 99%
“…in mammalian cells and tissues, and in bacteria (Gram-positive S. aureus and B. subtilis, and Gram-negative Citobacter sp. 5-77) [20,44,62]. Tsuchiya et al (2018) reported the reversible inactivation of Sa-GAPDH upon CoAlation [20].…”
Section: Sulfenylation and S-thiolation Of Gapdhmentioning
confidence: 99%
See 1 more Smart Citation
“…the formation of mixed disulfide bonds between small thiol‐containing compounds and protein cysteinyl thiol groups. Within the field of oxidative stress, mass spectrometry has been used to detect protein thiol oxidations such as to sulfenic acid, 20–23 sulfinic acid, 24 sulfonic acid, 25–27 S‐thiolation by coenzyme A, 28 hydrogen sulfide, 29 cysteine perthiosulfenic acid, 30 S‐nitrosylation, 31–34 cysteine 35,36 and glutathionylation, 37–40 and to a lesser extent protein S‐thiolation by HcySH 41,42 …”
Section: Introductionmentioning
confidence: 99%